ANALYSIS OF CELLULAR REACTION TO IFN-γ STIMULATION BY A SOFTWARE PACKAGE GeneExpressionAnalyser - A. V. Saetchnikov; M. M. Yatskou; P. V. Nazarov; L. Vallar; V. V. Apanasovich (Informatika)
The software package GeneExpressionAnalyser for analysis of the DNA microarray experi-mental data has been developed. The algorithms of data analysis, differentially expressed genes and biological functions of the cell are described. The efficiency of the developed package is tested on the published experimental data devoted to the time-course research of the changes in the human cell un-der the influence of IFN-γ on melanoma. The developed software has a number of advantages over the existing software: it is free, has a simple and intuitive graphical interface, allows to analyze different types of DNA microarrays, contains a set of methods for complete data analysis and performs effec-tive gene annotation for a selected list of genes.